Childhood depression: issues in definition diagnosis and assessment and the role of the teacher in early identification - Wessels, Jennifer S (Department of Psychology, 2024)
Until recently a little understood clinical phenomenon the very existence of which was questioned, depression is now considered a significant affective disorder in children (and adolescents). Given the grave consequences attendant upon childhood depression and the fact that early identification may be an important variable in prognosis, issues relating to its definition and identification are stressed in this dissertation. In an attempt to clarify controversies surrounding the definition of childhood depression (e.g. whether it is similar to adult depression or not) conceptual models of adult depression are put forward and their implications for childhood depression discussed. The question of how childhood depression can best be identified and other issues surrounding its assessment and diagnosis are examined. A brief review of measures used in assessment is also included as is a discussion of the use of the DSM-111(-R) with children. The role of the teacher in the early identification of childhood depression is explored and a more extensive role than is traditional, suggested. Limitations of the study and suggestions for future research are presented.